The influence of price, product, location, brand image and promotion on XYZ housing purchasing decisions - Sofyan, Haryanto; Sirait, Tongam (International Journal Labs, 2024)
The research aims to study the influence of price, product, location, brand image, and promotion on the decision to buy a house in XYZ housing, and is expected to make an important contribution in deepening the understanding of property market dynamics. The data collected were analyzed using the SPSS program. The results show that 81.1% of purchasing decisions can be explained by variables such as price, production, location and brand image and promotion. Moreover, the results of the F test indicate that the variables of price and product have no significant impact on purchasing decisions.